2021
DOI: 10.1371/journal.pone.0247106
|View full text |Cite
|
Sign up to set email alerts
|

Availability of adequately iodized salt at the household level in Ethiopia: A systematic review and meta-analysis

Abstract: Background Iodine deficiency disorder (IDD) is a global, regional, and national public health problem that is preventable. Universal salt iodization is a worldwide accepted strategy to prevent IDD. The level of iodine in the salt should be adequate at the household level (≥15ppm). Though there was fragmented evidence on the proportion of adequately iodized salt at the household level in Ethiopia, the national level proportion of adequately iodized salt at the household level was remaining unknown. Therefore, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
1
3
1
Order By: Relevance
“…However, only 48.5% were confirmed with ≥15 ppm iodine content in their daily salt which self-reported as they always used adequate iodized salt utilization. Which is considerably lower than the WHO recommendation levels to be 90%, 24 Pradesh Indian 48%, 25 Mayhew district (59.7%), 26 Dessie town 68.8%, 20 Asella town 76.8% in 2016, 27 Goba town 57.2%, 28 Dega Damot 88.8% 29 but higher than previous finding in 33.2% in Gondar, 30 33.5% in Addis Ababa, 16 and 25.7% in Ziway. 26 This might be due to the difference in whether there was a problem in the identification of iodized salt during purchasing from the whole sellers, shops, and others where iodized salt was sold and the lower global and regional levels.…”
Section: Discussioncontrasting
confidence: 59%
“…However, only 48.5% were confirmed with ≥15 ppm iodine content in their daily salt which self-reported as they always used adequate iodized salt utilization. Which is considerably lower than the WHO recommendation levels to be 90%, 24 Pradesh Indian 48%, 25 Mayhew district (59.7%), 26 Dessie town 68.8%, 20 Asella town 76.8% in 2016, 27 Goba town 57.2%, 28 Dega Damot 88.8% 29 but higher than previous finding in 33.2% in Gondar, 30 33.5% in Addis Ababa, 16 and 25.7% in Ziway. 26 This might be due to the difference in whether there was a problem in the identification of iodized salt during purchasing from the whole sellers, shops, and others where iodized salt was sold and the lower global and regional levels.…”
Section: Discussioncontrasting
confidence: 59%
“…The results also showed that 41.1% (CI95% 39.7%-42.2%) of households were covered with salt adequately iodized according to National standards, and 28.2% (CI95% 26.8%-29.6%) according to WHO standards [1]. This result is similar to a meta-analysis of 28 studies conducted between 2013 and 2020 in Ethiopia [12], from which it was found a combined coverage of 37% (95% CI: 28%-46%) as a proportion of households with adequately iodized salt (>=15 ppm). However, it was lower than the results of other studies conducted in South Africa and India, where coverage was 62.4% [13] and 75% [14], respectively.…”
Section: Discussionsupporting
confidence: 75%
“…This finding was lower than the study done in Addis Ababa City, which shows that 76.3% of households had good practice on iodized salt but higher than the study done in Tehran, which shows that the 14% of households had good practices on iodized salt [ 13 , 18 ]. Findings regarding to availability of iodized salt in the present study suggest that 41.7% of households have adequately iodized salt which was very lower than the WHO's recommendation according to which >90% of the households should utilize adequately iodized salt to eliminate IDD and in other developing countries like Kenya, Uganda, and Zimbabwe, which have successful household iodized salt coverage which is about 90% [ 4 , 19 ]. However, this finding is higher than study done in Gondar, North West Ethiopia in 2012, which was 28.9%, in Asosa, 26.1%, in Bale Goba, 30%, in rural of Ada District, 39%, and DHS, 2011, which showed that 23.2% of urban households have access to iodized salt [ 9 , 12 , 20 22 ].…”
Section: Discussionmentioning
confidence: 55%